Campur Kode dan Stereotip Masyarakat Kansai yang Tercermin dalam Lirik Lagu Kanjani Eight - Gresia Eliona; Titien Wahyu Andarwati (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2022)
Kanjani Eight is a Japanese idol group which all members are from the Kansai area. The songs of Kanjani Eight have a unique characteristic, namely the existence of code mixing and also imply the stereotypes of Kansai society in the song lyrics. The purpose of this study is to describe the kind of code-mixing and stereotypes of the Kansai society that implied in the lyrics of the Kanjani Eight song. The theories used in this study are sociolinguistic theory, code-mixing, and stereotypes of Kansai society. This study used qualitative research methods. The data sources of this research are the lyrics of the songs Takoyaki in My Heart and Osaka Obachan Rock which were popularized by Kanjani Eight. The data collection procedure in this study used the listening method and the advanced technique used was the note-taking technique. Then to analyze the data, the researcher used content analysis techniques. After conducting an analysis, it was known that the most dominant code mixing in the 2 lyrics of the song was internal code mixing. Inner code mixing found as many as 27 data while outer code mixing as many as 12 data. The stereotypes found in the 2 lyrics of the song are 12 out of 15 stereotypes, namely: likes joke, stingy, knowledgeable about food, gaudy, vulgar, never give up, folksy, traditional, friendly, shameless, proud of their dialect and love their home town. The domination of inner code mixing from 2 songs confirm stereotypes that Kansai society proud of their dialect. Keywords: code mixing; Kansai dialect; sociolinguistic; song; stereotype.